2023
DOI: 10.1088/1361-6463/acca8f
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown characteristics in dielectric-confined microcavity discharge of plate electrodes

Abstract: Breakdown characteristics in dielectric confined microcavity discharge of plate-to-plate electrodes under DC voltage are investigated in this paper. Experimental and PIC-MCC simulated results show that the breakdown characteristic curve (the relation of breakdown voltage Vbr with the product pd of gas pressure and electrode gap, or the Vbr-pd curve) with microcavity effect will deviate from the traditional Paschen curve, and seed electron adsorption by the dielectric wall is considered as the deviation mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In figure 3, the breakdown time delay at smaller height h = 300 µm is much higher than that at h = 2000 µm, which is due to the obvious increase of statistical time delay by microcavity effect. At p = 800 Pa, there is nearly no microcavity effect when h is 2000 µm [29]. When h is 300 µm, a large number of charged and excited species inside the microcavity are adsorbed by the dielectric wall during afterglow period, and then the appearance rate Y of initial secondary electrons from the cathode will be decreased.…”
Section: Memory Curves In Srpmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 3, the breakdown time delay at smaller height h = 300 µm is much higher than that at h = 2000 µm, which is due to the obvious increase of statistical time delay by microcavity effect. At p = 800 Pa, there is nearly no microcavity effect when h is 2000 µm [29]. When h is 300 µm, a large number of charged and excited species inside the microcavity are adsorbed by the dielectric wall during afterglow period, and then the appearance rate Y of initial secondary electrons from the cathode will be decreased.…”
Section: Memory Curves In Srpmentioning
confidence: 99%
“…For breakdown with microcavity effect, Wang et al [29] and Guo et al [30] studied the discharge characteristics of a flat electrode microcavity structure driven by DC voltage and found that the breakdown voltage will increase with the reduction of microcavity height, which is considered as a result of the electron adsorption by the microcavity wall [29]. Liu et al [31] and Curcio et al [32] studied the breakdown of capillary discharge by simulation and experiment, and obtained similar results of electron adsorption.…”
Section: Introductionmentioning
confidence: 99%